The relationships between work values ethic, design leadership and workplace innovation: A study of retailers in Malaysia - Wong, Kee-Luen; McMurray, Adela; Meunjohn, Nuttawuth; Teh, Hong-Leong (Advances in Social Sciences Research Journal, 2021)
This study examines the effect of design leadership behavior on the relationship between work values ethic and workplace innovation in Malaysia. Data were collected from 317 Malaysian retailer respondents. The instruments used to measure the three constructs were the Work Values Ethic (WVE) instrument, the Design Leadership Questionnaire (DLQ), and the Workplace Innovation Scale (WIS). Statistical Packages for Social Sciences (SPSS) and AMOS were used to analyze the data. We constructed the measurement models and structural models and found that both the design leadership (DL) and workplace innovation (WI) constructs were formative in nature. The results indicated that design leadership is a strong and significant mediator on the relationship between work values ethic and workplace innovation.